KEMAMPUAN SEPULUH STRAIN JAMUR MELAPUKKAN EMPAT JENIS KAYU ASAL MANOKWARI - Djarwanto; Sihati Suprapti; Freddy Jontara Hutapea (BRIN Publishing, 2018)
Capability of decaying-fungi varies according to their strains. This paper studies the decaying capability of ten fungi strains against four wood species from Manokwari. The wood samples have been exposed to the ten fungus strains using Kolle flask method as mentioned in SNI 7207: 2014. Scrutiny results revealed that two of ten fungus strains were categorized as low decaying capability, which comprised of Chaetomium globosum and Lentinus lepideus. Meanwhile, four strains were classified as moderate decaying capability which were Schizophyllum commune, Trametes sp. HHBI-379, Trametes sp. HHBI-332, and Phlebia brevispora. The remaining four fungus strains were regarded as high decaying capability, namely Polyporus arcularius, Polyporus sp., Pycnoporus sanguineus, and Tyromyces palustris. The highest weight loss of wood occurred in the sapwood of Rhus taitensis exposed to Polyporus sp. Meanwhile, the lowest loss was obtained on the heartwood of Haplolobus sp. caused by L. lepideus exposure. Three wood species comprising Tetrameles nudiflora, Rhus taitensis, and Pimeleodendron amboinicum belonged to non-resistant wood (class IV), while Haplolobus sp. was grouped into resistant wood (Class II).